2020
DOI: 10.3389/fnins.2020.00193
|View full text |Cite
|
Sign up to set email alerts
|

Leucine Rich Repeat Kinase 2 and Innate Immunity

Abstract: For more than a decade, researchers have sought to uncover the biological function of the enigmatic leucine rich repeat kinase 2 (LRRK2) enzyme, a large multi-domain protein with dual GTPase and kinase activities. Originally identified as a familial Parkinson's disease (PD) risk gene, variations in LRRK2 are also associated with risk of idiopathic PD, inflammatory bowel disease and susceptibility to bacterial infections. LRRK2 is highly expressed in peripheral immune cells and the potential of LRRK2 to regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 111 publications
0
32
0
Order By: Relevance
“…The currently available LRRK inhibitors mainly target LRRK2. The LRRK2 protein has two domains with catalytic activity; a GTPase domain of the Ras of complex (ROC) protein family, and a kinase domain of the tyrosine kinase like (TKL) family (79). Genome-wide association studies have linked kinase-activating mutations in LRRK2 with an increased risk for both Parkinson disease (80) and inflammatory bowel diseases (IBD) (81).…”
Section: Mining Beta Cell Molecular Footprints For Drug Re-purposing mentioning
confidence: 99%
“…The currently available LRRK inhibitors mainly target LRRK2. The LRRK2 protein has two domains with catalytic activity; a GTPase domain of the Ras of complex (ROC) protein family, and a kinase domain of the tyrosine kinase like (TKL) family (79). Genome-wide association studies have linked kinase-activating mutations in LRRK2 with an increased risk for both Parkinson disease (80) and inflammatory bowel diseases (IBD) (81).…”
Section: Mining Beta Cell Molecular Footprints For Drug Re-purposing mentioning
confidence: 99%
“…4 Cellular responses to bacterial infection mediated by RIPK7 (LRRK2). Sensing of LPS by TLR4 promotes localization of RIPK7 to endosomal membranes [ 225 , 226 ]. Here, RIPK7 can be exploited by M. tuberculosis (Mtb) to promote bacterial replication, as RIPK7 recruits Rubicon to the endosome, where this complexes with PI3K to prevent further phagosome maturation [ 222 ].…”
Section: The Role Of Ripk4 Ripk5 Ripk6 and Ripk7 In Pathogen Infectmentioning
confidence: 99%
“…The LRRK2 product is a multidomain protein kinase including an ankyrin repeat domain, a leucine‐rich repeat domain, a WD40 domain, and 2 catalytic domains, the GTPase domain of the Ras of complex protein family and the kinase domain of the tyrosine kinase like family 1 . The catalytic domains are of crucial importance for PARK‐ LRRK2 .…”
Section: The Protective Role Of Lrrk2 Kinase In Gut Immunity and Infementioning
confidence: 99%
“…Since then, at least 7 missense mutations (N1437H, R1441C/G/H, Y1699C, G2019S, I2020T) have been confirmed as pathogenic for PD, and genome‐wide association studies have consistently confirmed an association between PD risk and polymorphism in LRRK2 loci. Pathogenic mutations in LRRK2 are widely regarded as the most common cause of autosomal dominantly inherited PD (PARK‐ LRRK2 , OMIM 607060), 1 with variable age‐dependent penetrance (30%–74%) 2 . Here, we propose why PARK‐ LRRK2 should be considered a distinct, more benign form of PD.…”
mentioning
confidence: 92%